The role of duel hydrolysis of soybean on functional properties and protein digestibility: a sustainable approach - Jogi, Nishithkumar; Adusumilli, Somya; Nagesh, Madhukar; Yannam, Sudheer Kumar; Mamatha, Bangera Sheshappa (Frontiers in Nutrition, 2024)
Protein hydrolysates from food sources are composed of enormous number of peptides with amino acid chains exhibit several bioactive properties. However, the use of protein hydrolysates as a nutraceutical is hindered due to their unpleasant flavour. The study aims to enhance the biological activity and palatability of protein hydrolysatesIn the present study, soybean protein hydrolysates (SPH) was prepared using alcalase for 4h (control). Modification of hydrolysis (MPH) was carried by reiterating the hydrolysis of supernatant obtained after 2h of hydrolysis using enzyme to 50% of alcalase during each successive hydrolysis. Samples were characterised for their physio-chemical and functional properties. Further, the effect of modification on the protein digestibility and bitterness intensity using E-Tongue was studied. The suppressive effect on retrogradation of corn starch was analysed using Texture Profile Analysis.The results demonstrated an increased protein content by 1.6 and 1.9% in MPH compared to SPH and UNH respectively. MPH showed 1.5 and 1.6 folds higher DH% than SPH before and after gastrointestinal digestion (p<0.05). Decreasing in molecular weight was found in the order of UNH>SPH>MPH. Nevertheless, MPH displayed significantly higher functional properties (p≤ 0.05). The hardness of retrograded corn starch was significantly reduced in the MPH (1.21 N) than SPH (1.55 N) and UNH (1.81 N) compared to control (1.71 N) during 7day storage at 4 ºC (p≤0.05). E-tongue analysis of MPH showed four-fold reduction in bitterness than SPH.Modification of hydrolysis of soybean has demonstrated its significance in improved DH% functional properties and palatability. Additionally, improved protein digestibility with promising benefit in deferral action on retrogradation of starch over traditional process of hydrolysis was observed. The outcome of this study contributes to the potential utilization of MPH as an ingredient in the formulation of nutraceutical products.